Penatalaksanaan Holistik Pada Wanita Usia 59 Tahun dengan Hipertensi dan Dislipidemia Melalui Pendekatan Kedokteran Keluarga di Wilayah Kerja Puskesmas Tanjung Sari - Syafni, Alma Nazelia; Zuraida, Reni (CV. Jasa Sukses Abadi, 2024)
Based on data from the World Health Organization, it is estimated that around 15-20% of the world's population suffers from hypertension and data from the 2018 National Basic Health Research, there are 54.4% of the Indonesian population aged ≥ 15 years with cholesterol levels (≥ 200 mg/dl. Purpose of writing This is to apply the principles of family medicine services and carry out holistic management based on a framework for solving patient problems using a patient-centered, family focused and community oriented approach based on Evidence Based Medicine. This study is a case report. Internal risk factors were found, namely family history, unbalanced nutritional intake, and lack of knowledge of the disease. Ekxternal risk factors include lack of family knowledge about desease prevention and complication, lack of supervision over diet and medication. Patient Mrs. J, 59 years old, was diagnosed as grade I hypertension, dyslipidemia, and grade I obesity. In this case, diagnosis and treatment were carried out in accordance with theory and related journals. After the intervention was carried out, there was a reduction in clinical symptoms and an increase in patient and family knowledge. Holistic management can improve the knowledge, attitudes and behavior of patients and families in maintaining health.